Single-Ended Protection Scheme for VSC-Based DC Microgrid Lines - Cheng Lv; Xiaodong Zheng; Nengling Tai; Shi Chen (Energies, 2018)
With the promotion of distributed energy and direct current (DC) loads, the DC microgrid is able to provide a higher power quality and improve the grid efficiency. Various technical issues in DC microgrids are still to be addressed, particularly a proper protection scheme for fault detection and isolation in DC microgrids utilizing voltage source converters (VSCs). In this paper, the pole-to-pole DC fault transient behavior of the VSC-based microgrids is firstly analyzed with four successive stages, and then the exact requirements for protections are presented. Furthermore, a novel single-ended protection scheme based on local transient signals is proposed, which needs no data transmission or synchronization between two ends, ensuring the speed. A four-terminal DC microgrid model was built in PSCAD/EMTDC. Numerous simulations have demonstrated the validity of the proposed scheme.